Brachypodium distachyon as a model system for studies of copper transport in cereal crops - Jung, Ha-il; Gayomba, Sheena R.; Yan, Jiapei; Vatamaniuk, Olena K. (Frontiers in Plant Science, 2014)
Copper (Cu) is an essential micronutrient that performs a remarkable array of functions in plants including photosynthesis, cell wall remodeling, flowering, and seed set. Of the world's major cereal crops, wheat, barley, and oat are the most sensitive to Cu deficiency. Cu deficient soils include alkaline soils, which occupy approximately 30% of the world's arable lands, and organic soils that occupy an estimated 19% of arable land in Europe. We used Brachypodium distachyon (brachypodium) as a proxy for wheat and other grain cereals to initiate analyses of the molecular mechanisms underlying their increased susceptibility to Cu deficiency. In this report, we focus on members of the CTR/COPT family of Cu transporters because their homologs in A. thaliana are transcriptionally upregulated in Cu-limited conditions and are involved either in Cu uptake from soils into epidermal cells in the root, or long-distance transport and distribution of Cu in photosynthetic tissues. We found that of five COPT proteins in brachypodium, BdCOPT3, and BdCOPT4 localize to the plasma membrane and are transcriptionally upregulated in roots and leaves by Cu deficiency. We also found that BdCOPT3, BdCOPT4, and BdCOPT5 confer low affinity Cu transport, in contrast to their counterparts in A. thaliana that confer high affinity Cu transport. These data suggest that increased sensitivity to Cu deficiency in some grass species may arise from lower efficiency and, possibly, other properties of components of Cu uptake and tissue partitioning systems and reinforce the importance of using brachypodium as a model for the comprehensive analyses of Cu homeostasis in cereal crops.